2017
DOI: 10.2147/prbm.s146918
|View full text |Cite
|
Sign up to set email alerts
|

Acute alcohol effects on facial expressions of emotions in social drinkers: a systematic review

Abstract: BackgroundAs known from everyday experience and experimental research, alcohol modulates emotions. Particularly regarding social interaction, the effects of alcohol on the facial expression of emotion might be of relevance. However, these effects have not been systematically studied. We performed a systematic review on acute alcohol effects on social drinkers’ facial expressions of induced positive and negative emotions.Materials and methodsWith a predefined algorithm, we searched three electronic databases (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 95 publications
1
4
0
Order By: Relevance
“…Instead in adults, drinking to become more confident in social situations was identified as a negative reinforcement external drinking motive. The discovery of a confidence dimension supports previous research demonstrating alcohol being used as a social lubricant (Capito et al, 2017; Fairbairn & Sayette, 2014; Monahan & Lannutti, 2000). Social lubricants lower the fear of negative peer judgment and lead to social disinhibition and feelings of confidence (Fairbairn & Sayette, 2014).…”
Section: Discussionsupporting
confidence: 85%
“…Instead in adults, drinking to become more confident in social situations was identified as a negative reinforcement external drinking motive. The discovery of a confidence dimension supports previous research demonstrating alcohol being used as a social lubricant (Capito et al, 2017; Fairbairn & Sayette, 2014; Monahan & Lannutti, 2000). Social lubricants lower the fear of negative peer judgment and lead to social disinhibition and feelings of confidence (Fairbairn & Sayette, 2014).…”
Section: Discussionsupporting
confidence: 85%
“…The final behavioral output of these neurobiological and neurofunctional changes induced by alcohol intoxication is the impairment of various cognitive abilities due to globally reduced brain functioning. Indeed, many psychological and neuropsychological studies have reported that alcohol intoxication is related to a wide range of deficits encompassing visuo-motor (e.g., Poulsen et al, 2007), attentional (e.g., Nikolaou et al, 2013), memory (e.g., Wetherill & Fromme, 2011), inhibition (e.g., Field et al, 2010), higher-order executive (e.g., Spinola et al, 2017) or emotional (e.g., Capito et al, 2017) J o u r n a l P r e -p r o o f processes (see Zoethout et al, 2011 for a review). Beyond this negative impact on cognitive abilities, acute alcohol consumption is also thought to boost the salience of alcohol cues, through the exacerbated activation of the reward system.…”
Section: Introductionmentioning
confidence: 99%
“…For example, from a cultural perspective, alcohol is seen as a part of social life in western civilisation (Butcher et al, 2017). In celebrations, social events, and easing tensions, alcohol is often regarded as a "social lubricant" (Capito et al, 2017). In addition to the culture, it is stated that religious beliefs also affect addictions, but this effect has a more protective role, contrary to the example given above (Baena et al, 2019).…”
Section: Socio-cultural Causal Factorsmentioning
confidence: 99%